A baseline study of Fiji's small-scale lobster fishery using value chain analysis and size at maturity thresholds. (March 2023) - Tukana, Max; Prince, Jeremy; Glaus, Kerstin B.J.; Marama, Kalisiana; Whippy-Morris, Cherie
Abstract: Lobsters are an important catch component in Fiji's small-scale fisheries (SSF), but data are scarce. Seafood value chain analysis can provide insights on different actors involved in the fishery, thereby addressing human-wildlife interactions that may not otherwise be revealed. Data-poor SSF can further benefit from species-specific length-based spawning potential ratios and size at maturity thresholds deriving from relatively easily collectable data. In this study, 73 actors in the value chain of Fiji's lobster fishery were interviewed and 1636 individual lobsters across five species were measured. Lobsters are part of a multispecies fishery, mainly speared in reefs within traditional fishing grounds. The value chain is characterized by strong links among the key actors, but non-standardized units and non-uniform prices hamper the assessment of the actual income, profits and proportional values received. The length-based spawning potential ratio indicate that Panulirus penicillatus is around levels expected for a well-managed fishery, while Panulirus versicolor is vulnerable to being caught as juveniles, whereas estimates indicate a very high fishing mortality for Parribacus caledonicus . Thus, a focus on size-limitations and mitigation measures that allow P. versicolor and P. caledonicus to recover, is paramount, while SSF co-operatives based on community ownership can collaborate to generate economies of scale to increase the stability of the value chain. This study characterizes Fiji's small-scale lobster fishery, thereby providing a first mapping of the value chain, and allowing insights into the fishery's sustainability.